A MODEL‐BASED SYSTEMS ENGINEERING APPROACH TO RESILIENCY ANALYSIS OF AN ELECTRICAL DISTRIBUTION FACILITY. Issue 4 (December 2016) - Hecht, Myron J.
ABSTRACT: This article describes a model‐based systems engineering (MBSE) approach to cyberattack resilience modeling for an electrical power substation and demonstrates that (1) resiliency can be quantitatively characterized to enable design tradeoffs and (2) the analysis can be incorporated into a Systems Modeling Language (SysML) model to enable it to be incorporated into an MBSE development effort. The resiliency analytical model described here using the Markov model, derives from previous work on survivability analysis. For the system under analysis, it showed that the most important performance parameter for cyber resilience is propagation resistance followed by an attack rate mitigation. However, this applicability of this result is limited to this particular system with the parameter values described below. What is of more general importance is the value of such modeling, that when combined with SysML parametric analysis capability and the differential equation solvers in tools such as Matlab, has promise in improving resiliency with respect to cyber threats in the national energy.